Requirement of protein kinase type I for camp-mediated up-regulation of lipid-linked oligosaccharide for asparagine-linked protein glycosylation - Banerjee, D. K. (Cellular and Molecular Biology, 2007)
Glycan chains of asparagine-linked (N-linked) glycoproteins play a significant role in protein structure and function, as well as in angiogenesis an essential process for breast or other solid tumor growth. Non-availability of these chains causes incorrect folding of glycoproteins and leads to programmed cell death (i.e., apoptosis) through unfolded protein response (UPR) signaling. Cells actively processing cAMP signals modulate the glycan chain biosynthesis by PKA. Glycosylation of cellular proteins in a PKA type I-deficient CHO mutant 10248 was much reduced when compared with the wild type CHO 10001. The rate of LLO biosynthesis is similar in both cell types but quantitatively it is low in the mutant. Pulse-chase experiments indicated that the t for LLO-turnover in CHO 10248 was twice as high as that of the wild type. This correlated with the reduced DPMS activity. The Km for GDP-mannose for the DPMS activity was 3-4 folds higher in the mutant than that of the wild type with or without exogenously added Dol-P. The kcat of DPMS was also reduced in the mutant. In vitro phosphorylation of microsomes from the CHO 10248 by PKA, on the other hand, restored the DPMS activity to the normal level. The LLO biosynthesis also improved significantly in MR1, a revertant of the CHO 10248. The turnover of LLO in MR1 and the glycoprotein profile were also at par with the wild type. Therefore, we conclude that PKA type I plays an important role in modulating the protein N-glycosylation in cAMP responsive cells.